2011
DOI: 10.1038/npp.2011.248
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Neurochemical Adaptations Within the Nucleus Accumbens Produced by a History of Self-Administered vs Non-Contingently Administered Intravenous Methamphetamine

Abstract: Methamphetamine is a highly addictive psychomotor stimulant yet the neurobiological consequences of methamphetamine self-administration remain under-characterized. Thus, we employed microdialysis in rats trained to self-administer intravenous (IV) infusions of methamphetamine (METH-SA) or saline (SAL) and a group of rats receiving non-contingent IV infusions of methamphetamine (METH-NC) at 1 or 21 days withdrawal to determine the dopamine and glutamate responses in the nucleus accumbens (NAC) to a 2 mg/kg meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(75 citation statements)
references
References 112 publications
4
71
0
Order By: Relevance
“…The current findings not only show a similar meth-induced reduction in basal NAc GLU but also indicate that reduced basal cortical GLU levels likely contribute to the maladaptive balance in synaptic and extrasynaptic extracellular GLU activity in the corticostriatal pathway. Interestingly, a recent finding by Lominac et al (2012) reported that rats with a similar 2 h/day meth self-administration history followed by withdrawal showed an increase in basal NAc GLU levels. Notably, they measured GLU efflux following simple withdrawal at 1 day and 3 weeks, not after daily extinction sessions.…”
Section: Discussionmentioning
confidence: 98%
“…The current findings not only show a similar meth-induced reduction in basal NAc GLU but also indicate that reduced basal cortical GLU levels likely contribute to the maladaptive balance in synaptic and extrasynaptic extracellular GLU activity in the corticostriatal pathway. Interestingly, a recent finding by Lominac et al (2012) reported that rats with a similar 2 h/day meth self-administration history followed by withdrawal showed an increase in basal NAc GLU levels. Notably, they measured GLU efflux following simple withdrawal at 1 day and 3 weeks, not after daily extinction sessions.…”
Section: Discussionmentioning
confidence: 98%
“…Escalating meth self-administration increased basal levels of extra synaptic glutamate in the NAcore following 1–3 weeks of forced abstinence (Lominac et al, 2012). In contrast, basal levels of extracellular glutamate in the NAcore were reduced in meth self-administration animals that have also undergone extinction of the lever response (Parsegian and See, 2014), and presentation of meth-paired cues during reinstatement increased NAcore glutamate (Parsegian and See, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In noncontingently dosed rats the challenge decreased extracellular glutamate levels in the NAc, whereas in previously self-administering rats, an increase in glutamate levels was observed. This increase was also associated with a larger increase in DA levels (Lominac et al, 2012). Another study found reduced basal glutamate levels in both the NAc and PFC, but increased glutamate levels after reinstatement in self-administering rats compared with yoked saline controls (Parsegian and See, 2014).…”
Section: Action Of Substituted Amphetamines and Cathinonesmentioning
confidence: 90%